The silent tsunami: addressing community college food insecurity in Texas - Matthews, Lindy (Kansas State University, 2024)
This study explores the issue of food insecurity within community colleges in Texas and highlights administrator’s responses toward best and most promising practices and challenges in addressing food insecurity. The research was guided by complex adaptive systems theory and cynefin. Food insecurity among college students, especially community college students, continues to be a significant issue. Community colleges serve a diverse student population, including many low-income and underrepresented students who have a higher probability of experiencing food insecurity. However, community colleges receive less state funding and face challenges in addressing food insecurity among students. Food insecurity can negatively impact student success and completion rates. Providing appropriate resources to food insecure students will help community colleges close equity gaps and achieve their goals. However, identifying and assisting food insecure students remains challenging for community colleges. The purpose of this study was to identify best and promising practices for addressing food insecurity at community colleges and the challenges that administrators face in implementing these practices. The theoretical framework was complex adaptive systems theory, which views institutions as systems made of interdependent agents that interact and adapt. The conceptual framework was the cynefin framework, which categorizes situations as obvious, complicated, complex, or chaotic to guide decision-making. The researcher conducted a multisite case study of four community colleges with successful food insecurity resources through interviews, observations, and document analysis. The study was limited to community colleges in Texas. The study intended to inform best practices and institutional policies to help students facing food insecurity and contribute to the existing knowledge on community college food insecurity. This study examined food insecurity resources at four Texas community colleges. The findings revealed best practices such as campus buy-in, college foundation support, data-informed decision-making, and partnerships. Promising practices included community support, external grants, and leadership support. Emergent practices included employee training, location, marketing, and fully staffed departments. However, administrators faced challenges in implementing resources, such as lack of awareness and communication, insufficient staffing, limited space, and stigma. The similarities in findings across institutions of different sizes and locations suggest community colleges experience common challenges. The study provides recommendations to improve awareness, communication, and college foundation support to address food insecurity better.
The silent tsunami: community college food insecurity in Texas
Keywords: Food insecurity; Community college; Basic needs; Texas; Student success